The relationship between the applied torque and stresses in post-tension structures - Hamdan, S.; Liew, F.K; Osman, M.S (Universiti Malaysia Sarawak, UNIMAS, 2006)
This paper presents the non-destructive (NDT) method to determine the resultant stresses in mild steel bar usually employed in structures. The technique utilized ultrasonic pulse-echo that determined the wave velocity change due to torque applied between bolt and nut.